LEGAL FRAMEWORK FOR PREVENTING MONEY LAUNDERING FROM THE CIRCULATION OF VIRTUAL ASSETS - Starushchenko, Yaroslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the legal basis for preventing money laundering obtained from the circulation of virtual assets. Research methods: the chosen topic of scientific research requires the use of various scientific methods and approaches to obtain qualitative results. Therefore, the following research methods were used to solve the tasks: analysis; system method; analytical, etc. Results: the legal framework for preventing money laundering received from the circulation of virtual assets is in its infancy, and the current legislation of both the EU and other developed democracies in this area is still characterized by inconsistencies, contradictions, needs to eliminate gaps and does not provide optimal regulation of the digital market. However, for a comprehensive approach to eliminating gaps and inconsistencies in national legislation, the world The community has developed a number of recommendations to prevent money laundering received from the circulation of virtual assets. It is the preparation and implementation of the proposed norms that is the optimal step towards the development of appropriate national legal framework for the prevention of money laundering received from the circulation of virtual assets. Discussion: еffective policies and legal frameworks for the prevention of money laundering derived from the circulation of virtual assets are key to the integrity and stability of both the international and national financial system and economy. Money laundering and related crimes (so-called "predicate crimes") can threaten the integrity and stability of both the financial sector and the external stability of the country as a whole. They can lead to economic destabilization, banking crises, inefficient revenue collection, broader deficiencies in public administration, reputational risks to international financial centers, and the loss of correspondent banking relationships. In an increasingly interconnected world, the damage caused by these crimes is global and affects the integrity and stability of the international financial system. Digital technology is an integral part of any modern economy due to its high degree of productivity and technological capabilities. A distinctive feature of the Ukrainian economy is the introduction of digital technologies into everyday life, both to accelerate management decision-making and to achieve the goal of their implementation. It is worth pointing out that in the digital age, there is a rapid development in the use of virtual assets, which, among other things, contributes to the development of illegal activities.